Establishing a pure antiferroelectric PbZrO3 phase through tensile epitaxial strain - Krina Parmar; Pauline Dufour; Emma Texier; Cécile Carrétéro; Xiaoyan Li; Florian Godel; Jirka Hlinka; Brahim Dkhil; Daniel Sando; Hugo Aramberri; Jorge Íñiguez-González; Stéphane Fusil; et al. (Nature Communications)
Abstract The nature of lead zirconate, the historical antiferroelectric material, has recently been challenged. In PbZrO3 epitaxial films, thickness reduction engenders competition among antiferroelectric, ferrielectric and ferroelectric phases. All studies so far on PbZrO3 films have utilized commercially-available oxide single crystals with large compressive lattice mismatch, causing the films to undergo strain relaxation. First-principles calculations have predicted that tensile strain can stabilize antiferroelectricity down to the nanometre scale. Here we use tensile strain imposed by artificial substrates of LaLuO3 to stabilize a pure antiferroelectric phase in PbZrO3. Sharp double hysteresis loops of polarization vs electric field show zero remanent polarization, and polar displacement maps reveal the characteristic up-up-down-down antipolar pattern down to 9 nanometre film thicknesses. Moreover, the electron beam can move this antipolar pattern through the nucleation and annihilation of translational boundaries. These results highlight the critical role of coherent epitaxial strain in the phase stability of PbZrO3.